Determination of trace elements (As, Ca, Cu, Fe, Pb, Zn) and identification of Clostridium perfringens in honeys originated from different region of Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2017)
Trace elements and heavy metal residues in honey samples originating from different regions of Bangladesh were determined. High mineral contents were observed with Ca, and Fe being the most abundant. The concentrations of the trace elements were within the recommended limits, indicating that the honeys were of good quality. Pb was present in trace amount which is not harmful for consumption where Arsenic was absent. Clostridium perfringens spores were not found in the analyzed honey samples.Jahangirnagar University J. Biol. Sci. 5(2): 11-14, 2016 (December)